Architecting Datacenters for Sustainability: Greener Data Storage using Synthetic DNA - Nguyen, Bichlien; Sinistore, Julie; Smith, Jake; Arshi, Praneet S.; Johnson, Lauren M.; Kidman, Tim; diCaprio, T.J.; Carmean, Doug; Strauss, Karin (Electronics Goes Green 2020, 2020)
Global digital data generation has been growing at a breakneck pace. Although not all generated data needs to be stored, a non-trivial portion does. Synthetic deoxyribonucleotide acid (DNA) is an attractive medium for digital information storage. If kept under appropriate conditions, DNA can reliably store information for thousands of years. It also has a practical estimated density of 1 Exabyte per cubic inch, which is much higher than commercial data storage media. Buildings, infrastructure, electronic computing, storage, and networking equipment, and other physical resources all contribute to the environmental impacts, particularly, emissions, energy and water consumption, and waste generation of digital data storage. DNA data storage has the potential to limit these impacts by drastically reducing the resources required to maintain very large volumes of data. In this paper, we describe how to store digital information in synthetic DNA, present a cradle-to-grave life cycle assessment (LCA) of archival DNA data storage, and compare the resulting environmental impacts with those of traditional hard disk drives (HDDs) and tape storage based on greenhouse gas (GHG) emissions, energy usage, and blue water consumption (BWC). We conclude that DNA shows promise when compared to HDDs and tape, and we follow that conclusion with a discussion of how further innovation in biotechnology could be used to improve the sustainability of future datacenters.